Dicer ablation in Kiss1 neurons impairs puberty and fertility preferentially in female mice - Roa Juan; Ruiz-Cruz Miguel; Ruiz-Pino Francisco; Onieva Rocio; Vazquez Maria J.; Sanchez-Tapia Maria J.; Ruiz-Rodriguez Jose M.; Sobrino Veronica; Barroso Alexia; Heras Violeta; Velasco Inmaculada; Perdices-Lopez Cecilia; et al. (NATURE PORTFOLIO, 2022)
Kiss1 neurons, producing kisspeptins, are essential for puberty and fertility, but their molecular regulatory mechanisms remain unfolded. Here, we report that congenital ablation of the microRNA-synthesizing enzyme, Dicer, in Kiss1 cells, causes late-onset hypogonadotropic hypogonadism in both sexes, but is compatible with pubertal initiation and preserved Kiss1 neuronal populations at the infantile/juvenile period. Yet, failure to complete puberty and attain fertility is observed only in females. Kiss1-specific ablation of Dicer evokes disparate changes of Kiss1-cell numbers and Kiss1/kisspeptin expression between hypothalamic subpopulations during the pubertal-transition, with a predominant decline in arcuate-nucleus Kiss1 levels, linked to enhanced expression of its repressors, Mkrn3, Cbx7 and Eap1. Our data unveil that miRNA-biosynthesis in Kiss1 neurons is essential for pubertal completion and fertility, especially in females, but dispensable for initial reproductive maturation and neuronal survival in both sexes. Our results disclose a predominant miRNA-mediated inhibitory program of repressive signals that is key for precise regulation of Kiss1 expression and, thereby, reproductive function.Kiss1 neurons are essential for puberty and fertility. Here, the authors show that canonical microRNA biosynthesis in Kiss1 neurons plays an essential role in the control of puberty and fertility, especially in females, likely via repression of repressors on the Kiss1 gene.